Examining the Impact of Compensation and Competency on Elementary School Teacher Performance - Zainal Arifin (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teacher competence in schools is still not optimal because the average teacher competence is below 50%, especially in pedagogical, personal, and social competence. The compensation given to teachers who teach is still not optimal; the average amount offered does not meet the principles of justice. The average basic salary is 42.4%, and allowances are 57.6%, which consists of primary, functional, teaching, and transport allowances. This research analyzes the relationship between competence, compensation, and teacher performance in elementary schools. The research method uses a quantitative approach with a non-experimental correlational design. There were 40 respondents (non-permanent teachers) in the research using a non-probability sampling method. The data collection technique uses a survey method with closed questionnaire tools. Data analysis was carried out using validity tests, reliability tests, descriptive analysis, and multiple linear regression analysis. The research results show that the regression coefficient analysis of the competency variable (0.018) and compensation variable (0.025) significantly affects performance. Research results: The better the teacher's competence, the more the teacher's performance will increase. The implication is that the competency of elementary school teachers needs to continue to be improved in various ways, one of which is through continuous teacher professional development programs, both independently and with managerial encouragement from school principals.